(untitled) - Newman, Christy M. (Boston, MA., 2006)
Strategies for Test-Taking Success is an innovative test preparation series designed to help all students develop effective test-taking skills and strategies, regardless of their English language proficiency or academic level. Each book in the Strategies series focuses on a major testing discipline.
Keywords: English language,Report writing,English language,English language; Rhetoric,Problems, exercises, etc.,Problems, exercises, etc.,Examinations